What can I do? : my path from climate despair to action - Fonda, Jane, 1937- (Penguin Press, 2020)
"In the fall of 2019, frustrated with the obvious inaction of politicians and inspired by Greta Thunberg, Naomi Klein, and student climate strikers, Jane Fonda moved to Washington, DC to lead weekly climate change demonstrations on Capitol Hill. On October 11, she launched Fire Drill Fridays (FDF), and has since led thousands of people in non-violent civil disobedience, risking arrest to protest for action. In her new book, Fonda weaves her deeply personal journey as an activist alongside interviews with leading climate scientists, and discussions of specific issues, such as water, migration, and human rights, to emphasize what is at stake. Most significantly, Fonda provides concrete solutions, and things the average person can do to combat the climate crisis in their community. No stranger to protest, Fonda's life has been famously shaped by activism. And now, on the eve of the next presidential election, she is once again galvanizing the public to take to the streets. Too many of us understand that our climate is in a crisis, and realize that a moral responsibility rests on our shoulders. 2019 saw atmospheric concentrations of greenhouse gases hit the highest level ever recorded in human history, and our window of opportunity to avoid disaster is quickly closing. We are facing a climate crisis, but we're also facing an empathy crisis, an inequality crisis. It isn't only earth's life-support systems that are unraveling. So too is our social fabric. This is going to take an all-out war on drilling and fracking and deregulation and racism and misogyny and colonialism and despair all at the same time"--